Changing of the legal status of drug products in the Polish pharmaceutical market - Joanna Ronowicz (Polish Pharmaceutical Society, 2020)
It can be observed that the legal status of many prescription medicines is being changed to over-the-counter drug products in the Polish pharmaceutical market. This situation creates the possibility of advertising these OTC drugs and consequently, it leads to increased sales and financial benefits for the marketing authorization holder. The increasing availability of OTC drugs makes the self-treatment of patients possible. In this way, public spending on healthcare in Poland may be also reduced. A changing of the legal status from prescription drugs to OTC drugs is called a switch. The legal acts describe in detail a way of drug products qualification to a certain category which is also specified in the marketing authorization. The marketing authorization holder may submit an application for a change in the legal status of a drug product to the President of the Office for Registration of Medicinal Products, Medical Devices and Biocidal Products. The Commission for Medicinal Products provides an opinion on the application submitted by the marketing authorization holder. In recent years, many prescription medicines have changed their legal status to OTC drugs. This so called switch often raises concerns and controversies among doctors and pharmacists. Each drug product may indicate some adverse drug reactions and may also interact with food and other medicines. An increased product availability by changing the legal status to OTC drugs may increase the risk of drug abuse. There is also a risk of using medicines inconsistently with the therapeutic indication or a risk of using drug products for a too long time period. The legitimacy of using OTC drug products should be supervised by the pharmacist dispensing drugs from a community pharmacy. There is no doubt that the availability of OTC drugs may lead to reduce public spending on healthcare in Poland. However, health education of patients is undoubtedly an essential element of responsible self-treatment in which doctors as well pharmacists should be committed.